ENT300 Fundamental of Enterpreneurship MaiDah Enterprise / Abid Arif Abd Rashid...[et al.] - Abd Rashid, Abid Arif; Mohd Radzi, Ahmad Salihin; Mansor, Hilman Hanif; Abd Radak @ Abdul Razak, Muhammad Daniel; Amir Ruddin, Muhammad Adam Fuzzery (2019)
MaiDah Enterprise is a business that design an application services that purposely to reduce problems facing by non-residents students in UiTM. We provide Track the location of bus (GPS), Arriving of bus (Time), Amount of passengers (Availability) and passengers can pin their location (Pin). Our target’s customers are non- residents students. We sell our product services at RM 4.99. Based on the targeting customer, we identifying the customers are from Diploma and Degree students from different semester. This business is based on partnership where it consists of five members who hold important positions in the company such as General Manager, IT Manager, Marketing Manager, Operation Manager and Financial Manager. The total contribution of each member for the business purposes is RM 14300. We are hoping and wishing to make MaiDah application service be able to provide connectivity with the user and helps them to solve problem facing. Our business is expected to commence on 18 December 2020. The members are basically from Diploma graduation have their own capabilities. The five partners will be take responsibilities based on their different duties and work’s portfolio.